Development of an Evaluation Model for Islamic Religious Education and Character Education (PAI-BP) at The High School Level: Between Urgency and Effectiveness - Ahmad Muhtadi; Mulyoto Mulyoto; Dardiri Hasyim (Journal Research of Social Science, Economics, and Management, 2023)
The research is aimed to: (1) identify a factual model of learning evaluation of Islamic Religious and Moral Education (PAI-BP); (2) develop the PAI-BP learning evaluation model to suit the needs of the high school education level; and (3) knowing and analyzing the effectiveness of the PAI-BP learning evaluation development model at the high school education level in Karanganyar Regency for the 2020/2021 academic year. The type of the research is development research targetting the evaluation model for Islamic Religious and Moral Education (PAI-BP) for high school level. The data collection method was done using observation, in-depth interviews, document analysis, tests, and questionnaires techniques. Data analysis was carried out by qualitative and quantitative analysis. The research concluded that: (1) The factual model of the evaluation of Islamic Religious Education and Moral Education (PAI-BP) at the high school education level currently done separately between the process of learning and its product; (2) The evaluation model developed has two main components, namely: the learning process and output. The learning process includes four subcomponents, namely: (a) teachers’ performance in the classroom, (b) teachers’ personality, (c) students’ behavior, and (d) learning facilities. Whereas the learning output includes four sub-components, namely aspects: (a) akidah akhlaq, (b) Qur'an-Hadith, (c) Fiqh, and (d) Islamic history; and (3) The effectiveness of the PAI-BP learning evaluation model developed shows that based on the experts, user and practitioner assessments, the model developed is considered as a Good model to evaluate PAI-BP learning at high school level education.